AKTIVITAS FILANTROPI ISLAM DI KALANGAN JAMA’AH TABLIGH HALQAH SIPISPIS KABUPATEN SERDANG BEDAGAI SUMATERA UTARA - Ibnu Radwan Siddik (TAQNIN: Jurnal Syariah dan Hukum, 2019)
Philanthropy (generosity) is part of Islamic teachings. The form of Islamic philanthropy in the form of charity is found in zakat, infaq, alms and endowments. While philanthropy in the form of non-charity is found in an attitude of helping and glorifying fellow Muslims. In its implementation, Islamic philanthropic activity is relatively still not getting the attention of the Islamic community in Indonesia. This condition is a little different if we look at philanthropic activities among the Tablighi Jama'ah, especially in the Serdang Bedagai Regency Sipispis. This research aims to explore the activities of Islamic philanthropy among the Tablighi Jamaat Halqah Sipispis Jama'ah of Serdang Bedagai Regency in North Sumatra, whatever forms of Islamic philanthropy are carried out and the factors underlying the spirit of Islamic philanthropy. By using a legal sociology approach and analyzed qualitatively it can be concluded that philanthropic activities among the Tablighi Jamaat halqah Sipispis of Serdang Bedagai Regency run continuously following the missionary effort. The forms of philanthropic activities include Khuruj funds, khidmad funds, funds for wives left to preach, Khidmad Markaz funds, zakat and other social assistance funds. This philanthropic activity is carried out with enthusiasm because the socialization of the importance of Islamic philanthropy for the afterlife of the world is always carried out in taklim and lectures (bayan) when participating in the Jamaah Tabligh da'wah program.